Estudio comparativo de la viabilidad técnico-financiera entre la tecnología convencional y la tecnología full length ultrasonic technology de inspección para tubería de perforación entre 3 1/2 "Y 5 " en el pozo loto 2 en el bloque CPO-5 (2016)
In this paper grade implementation of technology was held FLUT, the results of this correlated with conventional technology where are the times of pipeline inspection are reduced compared to the conventional technology it held by the company, in addition to providing v more quality information about pipe before and after drilling. The cost-benefit financial indicator m evaluated for application of technology "full length ultrasonic technology" compared to conventional technology, very positive results have, ensuring profitability for the company inspector.